Pengaruh Pelatihan dan Pengembangan SDM Terhadap Kinerja Karyawan Bank Syariah Indonesia Kc. Bandar Lampung Kedaton - Hasrun Afandi UmpuSinga; Atika Riasari; Dwi Hana Ria Qoyum (Al-Buhuts, 2022)
Training and development has an important role to improve employee performance and improve quality human resources. The purpose of the study was to determine the effect of simultaneous and partial HR training and development on the performance of Indonesian Islamic bank kc employees. Bandar Lampung, Kedaton. This type of research used a quantitative approach to determine the effect of the independent variable, namely training (X1) and development (X2) on the dependent variable, namely employee performance (Y). The sample used is the employees of sharia indonesia kc. Bandar Lampung Kedaton with a total of 31 employees. The sampling technique used was a purposive sample and a questionnaire which was used as primary data. The method used to collect respondent data is a questionnaire with a Likert scale. Data analysis used multiple linear regression analysis which was processed with SPSS 20. The results of this study based on data analysis of hypothesis testing that was carried out partially, the training variable (X1) had no effect and the development variable (X2) had an effect. Simultaneously, training variables (X1) and development (X2) affect employee performance.